(untitled) (Research, Society and Development, 2022)
Titanium and its alloys are widely used as biomaterials in hard tissue replacements due to their unique physiological environment responses and chemical and mechanical properties, such as corrosion resistance, fatigue resistance, and ductility. Other metals used as biomaterials have elastic modulus with values ​​ten times higher than human bone, which can cause failure when there are impacts. Several studies report hip prosthesis failures due to fatigue. This article aims to carry out studies on the mechanical properties and fatigue resistance in an environment that simulates those of the joints of the human body, using hip prostheses manufactured with Ti 6Al 4V alloy with hydroxyapatite coating. Samples were taken from the neck region for microstructural characterization to identify grain size, inclusions, microhardness, tensile test, scanning electron microscopy, energy dispersion spectroscopy, X-ray fluorescence,e, and X-ray diffraction also performed. After applying more than 10,000,000 cycles with compressive forces ranging from -0.3 kN to -3.0 kN, no cracks were found and it was observed that the part suffered only elastic deformations.